Fracture toughness modelling of polymers filled with inhomogeneously distributed rigid spherical particles - B. Lauke (eXPRESS Polymer Letters, 2017)
Filler particles are not homogeneously distributed in real composites consisting of polymer matrices and rigid spherical particles. In the presence of a crack, high multiaxial stresses develop in the material which are a function of the distance from the crack tip. This variation effects the stress concentration in the periphery of the inhomogeneously distributed particles. For a certain stress level closer particles are able to debond from the matrix while particle pairs with larger centre to centre distances may still be bonded to the matrix. Based on a two particle model, the debonding and matrix yielding energies were calculated. Subsequent integration over the local composite deformation results in the fracture toughness of such composites. Randomly distributed particles provide a lower fracture toughness in modelling as compared to inhomogeneoulsy distributed particles in the composite.